Serum Levels of VWF, t-PA, TNF-α, and ICAM-1 in Patients Receiving Hemocoagulase Combined with Platelet-Rich Plasma during Total Hip Replacement - Yaobin Huang; Bin Zhou; De Zhang; Yu Chen (Genetics Research)
Objectives. This study aimed to investigate the effect of hemocoagulase combined with platelet-rich plasma (PRP) in total hip replacement (THR) on reducing bleeding and improving knee joint function in the patients with osteoarthritis. Methods. From February 2018 to February 2020, 80 osteoarthritis patients undergoing THR were included in the study, of which 40 cases were treated with PRP and hemocoagulase (test group) in the joint capsule in THR and the other 40 cases received saline and thrombin in the joint capsule after THR (control group). Postoperative drainage and corresponding functional exercise were performed for the two groups 12 hours after operation. The outcome measures including operation time, soft-tissue release, blood routine, drainage volume, perioperative blood loss, postoperative incision inflammation, deep vein thrombosis (DVT), and range of motion (ROM) of the joint were recorded. Results. The hemoglobin and hematocrit values of the test group on the second postoperative day were significantly higher than those of the control group (P<0.05). The postoperative drainage volume and perioperative blood loss were significantly lower than those of the control group (P<0.05). The test group was better than the control group in the ROM of the joint at 7 and 15 days after the operation (P<0.05). A lower value of prothrombin time and activated partial thromboplastin time was revealed in the test group compared with the control group (P<0.05). No significant difference in the operation time, intraoperative soft-tissue release, postoperative incision inflammation, incidence of DVT, incidence of deep infection, and ROM at day 90 after THR was found in the two groups (P>0.05). Conclusions. The application of hemocoagulase combined with PRP in THR can reduce perioperative blood loss, increase wound healing speed and quality, and improve coagulation and immune function. It is a safe and effective method for the patients with knee osteoarthritis who underwent THR.